Exploring the Intersectionality of Teenage Pregnancy, Rights, and Sexuality Education: A Case Study Analysis in Tugbok, Davao City - Elleyza L. Duka (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This research sought to investigate the interplay between teenage pregnancy, human rights, and sexuality education in the Tugbok, District of Davao City. In spite of being such an important problem as that of teen pregnancy is, there seems to be very little attention given to it, especially when one takes into consideration poor and marginalized societies. There are several causes for teen pregnancy, such as peer pressure, poverty, internet, lack of parents' guidance, and poor or no knowledge of proper sexuality education at all. The qualitative case study approach was chosen for this research with semi-structured interviews conducted among four purposively sampled mothers aged between 17 and 19 who come from poor backgrounds as out-of-school youths in Tugbok District. From the thematic analysis, the following results emerged; First, dire poverty severely influenced the agency of the respondents, pushing some of them to engage in prostitution for economic reasons. Second, all respondents reported experiencing social stigma from their communities, leading to psychological problems like depression and even thoughts of committing suicide. Lastly, there was a major conflict about the necessity of sexuality education. While all acknowledged its practical benefits in preventing the spread of sexually-transmitted diseases, majority of the group members were opposed to the idea of its incorporation in schools at the primary level due to concerns of promoting early sexual experimentation and respect for the autonomy of adolescents in making their decisions.